Analysis of Mixing Used Oil with Solar As Fuel Against Smoke Thickness in Diesel Motors - Iffarial Nanda; Martias Martias; Toto Sugiarto (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2019)
Effect of the precision of smoke of diesel motor vehicles by utilizing used oil mixed with diesel fuel. The purpose of this study is to know the mix up to what percentage of used oil that can be used as fuel to the precision of diesel motor fume in accordance with the limits of regulation of the Ministry of Environment No. 05 of 2016. For testing of Smoke thickness using gauge opacity smokemeter, used is used oil 5% mixed with solar 95%, used oil 10% mixed diesel 90%, used oil 15% mixed with diesel 85%, used oil 20% mixed 80% solar, used oil 40% mixed diesel 60%, oil used 60% mixed 40% solar, 80% used oil mixed with 20% diesel, and 100% used oil. at acceleration engine speed Acceleration is done three times on each sample and then compare for each samples tested. From result of research can be concluded that semekin big percentage of mixing of used oil hence influence to smoke thickness in Isuzu Panther diesel motor. The used oil mixture of 5% to 40% of the resulting smoke thickness is still within the threshold of the exhaust emissions in accordance with Regulation of the Ministry of Environment No. 5 of 2006 which is smoke thickness below 70%.